Practices, Challenges and Interventions in Teaching Kindergarten Curriculum in Diadi District, SDO Nueva Vizcaya - Yogyog, Jovelyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the practices, challenges, and interventions in teaching the kindergarten curriculum in Diadi District, SDO Nueva Vizcaya. Anchored on the concepts of developmentally appropriate practice and curriculum implementation fidelity, the study focused on how the kindergarten curriculum was translated into actual classroom practice and how implementation concerns may be addressed. It employed a research design appropriate for describing existing practices, challenges, and interventions related to kindergarten curriculum implementation. The study was conducted in Diadi District under the Schools Division Office of Nueva Vizcaya and involved respondents directly engaged in teaching and implementing the kindergarten curriculum. Data were gathered through a research instrument designed to capture teaching practices, implementation challenges, and proposed interventions. The findings showed that teaching practices in kindergarten curriculum implementation were generally high, with strong results in child-centered teaching, developmentally appropriate classroom activities, and curriculum responsiveness. However, substantial challenges remained, particularly in limited instructional materials, diverse learner needs and readiness, insufficient time to accomplish activities, parental follow-up, and consistency of curriculum delivery. The results also revealed very high support for interventions such as school-based and district-level professional development, provision of developmentally appropriate instructional materials, collaborative lesson planning, instructional coaching, and stronger parent-school coordination. A positive and significant relationship was found between the level of implementation challenges and the level of support for interventions, indicating that greater implementation difficulties were associated with stronger demand for sustained support. The study concluded that kindergarten curriculum implementation in the district was generally strong in practice but constrained by contextual and institutional barriers. It is recommended that support mechanisms be strengthened through continuous professional development, resource provision, collaborative planning, and home-school coordination. The study is directly aligned with SDG 4 – Quality Education and has a secondary connection to SDG 10 – Reduced Inequalities. Its sustainability impact lies in strengthening educational and institutional sustainability by supporting more responsive, equitable, and context-sensitive kindergarten instruction in public schools
Keywords: Child-Centered Teaching, Curriculum Implementation, Early Childhood Education, Kindergarten Curriculum, Professional Development, School Readiness, Teaching Practices